Extended self: "Техника себя" в современном мире; Векторы благополучия: экономика и социум; № 1 (40) - Конюхова Т. В. Татьяна Васильевна; Конюхова Е. Т. Екатерина Тимофеевна; Лукьянова Н. А. Наталия Александровна; Су-Тинг Чен; Кай-Юань Чэн (Гуманитарные науки, 2021)
Заглавие с титульного листа